Maximal independent sets in trees with large maximum degree - Jin, Zemin; Liang, Xiaoying; Liu, Xuezi (Utilitas Mathematica, 2009)
In this paper we determine the number of maximal independent sets in a tree with large maximum degree. Extremal trees achieving these values are also determined.